Work Discipline for Badan Kesatuan Bangsa dan Politik Office of Mojokerto Regency - Siska Dwiky Anggraini; Saiman Saiman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The aims of this study are: 1) To find out how the discipline of employees in improving employee performance at the office of the National Unity and Politics of Mojokerto Regency, 2) To find out the obstacles faced in disciplining employees at the Office of National Unity, Politics and Community Protection, Mojokerto Regency. . The type of research is qualitative research with a descriptive approach. Based on the results of the study that: 1) The division of tasks for civil servants at the National Unity and Political Agency of Mojokerto Regency is based on Regional Regulation number 10 of 2010 concerning the organizational structure of the Mojokerto Regency National and Political Unity Agency, which the organizational structure itself consists of the head of the agency. , secretariat and functional position groups, 2) The work discipline of employees at the National Unity and Political Agency of Mojokerto Regency has not run according to existing regulations, there are still many employees who do not carry out the discipline so that it greatly affects employee performance, especially in service to the community, and 3) The quality of employee performance at the National Unity and Political Agency of Mojokerto Regency has been running very well, while the quantity of employee performance cannot be said to be good because it has not been realized as a whole. 4) The obstacles that arise in improving employee work discipline include the number of employees who get external service assignments so that leaders find it difficult to carry out direct supervision and loyalty to the corps (esprit de corps) which often makes the authorized superiors impose light sanctions  disciplinary subordinates.